The Fragile Benefits of Endowment Destruction - Campbell, John Y.; Cochrane, John H. (Journal of Political Economy, 2015)
The benefits of endowment destruction documented by Ljungqvist and Uhlig (2015), and the related possibility that consumption can lower habits, are fragile. Both issues result from a particular way of discretely approximating the underlying continuous-time model or of adapting it to jumps. Other ways of calculating the discrete-time approximation or extending the model to jumps easily overturn the results, while making no difference to the model's description of asset prices and quantities. This analysis gives an example of how to extend models so that the jump gives the same result as a jump limit of continuous-sample-path movements.